Protein Coding Palindromes Are a Unique but Recurrent Feature in Rickettsia - Ogata, Hiroyuki; Audic, Stéphane; Abergel, Chantal; Fournier, Pierre-Edouard; Claverie, Jean-Michel (Genome Research, 2002)
Rickettsia are unique in inserting in-frame a number of palindromic sequences within protein coding regions. In this study, we extensively analyzed repeated sequences in the genome ofRickettsia conorii and examined their locations in regard to coding versus noncoding regions. We identified 656 interspersed repeated sequences classified into 10 distinct families. Of the 10 families, three palindromic sequence families showed clear cases of insertions into open reading frames (ORFs). The location of those in-frame insertions appears to be always compatible with the encoded protein three-dimensional (3-D) fold and function. We provide evidence for a progressive loss of the palindromic property over time after the insertions. This comprehensive study of Rickettsia repeats confirms and extends our previous observations and further indicates a significant role of selfish DNAs in the creation and modification of proteins.
10.1101/gr.227602